Characteristics and outcomes of cholangiocarcinoma by region in Thailand: A nationwide study - Chaiteerakij, R; Pan-Ngum, W; Poovorawan, K; Soonthornworasiri, N; Treeprasertsuk, S; Phaosawasdi, K (Bashideng Publishing Group, 2017)
Aim To identify the potential risk factors of cholangiocarcinoma, we determined the characteristics of cholangiocarcinoma patients among 5 different regions of Thailand. Methods All patients diagnosed with cholangiocarcinoma between 2008 and 2013 were identified using the Nationwide Hospital Admission Data registry (n = 39421). Baseline characteristics, comorbidities and survival were abstracted. Results The annual incidence during the study period was stable in all regions. Most patients lived in the Northeast (62.8%), followed by the North (16.9%), Central (12.3%), Bangkok (5.4%), and South (n = 2.6%) regions (p < 0.0001). Significantly more cholangiocarcinoma patients had diabetes, cirrhosis, and chronic viral hepatitis B/C infection than noncholangiocarcinoma participants (diabetes: 11.42% vs 5.28%; cirrhosis: 4.81% vs 0.92%; hepatitis B: 0.74% vs 0.12%; and hepatitis C: 0.50% vs 0.10%, p < 0.0001 for all, respectively). The overall 1-year mortality rate was 81.7%, with a stable trend over time. Conclusions Diabetes and chronic liver diseases may be associated with cholangiocarcinoma in the Thai population.